2019
DOI: 10.3390/mi10050320
|View full text |Cite
|
Sign up to set email alerts
|

Tangential Flow Microfiltration for Viral Separation and Concentration

Abstract: Microfluidic devices that allow biological particle separation and concentration have found wide applications in medical diagnosis. Here we present a viral separation polydimethylsiloxane (PDMS) device that combines tangential flow microfiltration and affinity capture to enrich HIV virus in a single flow-through fashion. The set-up contains a filtration device and a tandem resistance channel. The filtration device consists of two parallel flow channels separated by a polycarbonate nanoporous membrane. The resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Reproduced under the terms of the CC‐BY Creative Commons Attribution 4.0 International License. [ 80 ] Copyright 2019, MDPI Open Access Journals.…”
Section: Microfluidic Sample Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced under the terms of the CC‐BY Creative Commons Attribution 4.0 International License. [ 80 ] Copyright 2019, MDPI Open Access Journals.…”
Section: Microfluidic Sample Processingmentioning
confidence: 99%
“…In another example, Wang et al used tangential flow microfiltration on the chip to separate/concentrate the HIV (Figure 5). [80] The top tandem resistance and bottom permeate channels were separated with a NeutrAvidin functionalized polycarbonate (PC) nanoporous filter (pore size ≈50 nm). As shown in Figure 5c, when the top resistance channel enhances filtration, the fluid partially enters the top channel and then moves tangentially toward the filter.…”
Section: Physical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight papers are published in this special issue and cover the design of microfluidics for bioseparation [1,2,3,4,5,6], incorporation of sensors with microfluidics for particle detection [6,7], and modular devices with both functions [1,6,7]. Nanomaterials have been combined with microfluidics for both separation [5] and sensing [7] purposes. The special issue also includes a review on programmable paper-based microfluidics [8].…”
mentioning
confidence: 99%
“…The collection of papers describe a wide spectrum of separation and sensing mechanisms. For example, Wang et al [5] incorporated nanoporous membranes into microfluidic channels, and demonstrated the separation and enrichment of virus from biological fluids through nanofiltration. Yang et al [6] took advantage of particle inertia in curved microfluidic channels to separate and contain particles in micro-tanks, which were further resolved by optical diffraction.…”
mentioning
confidence: 99%